2021
DOI: 10.1016/j.sjbs.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of a multistrain potential probiotic, formic, and lactic acids with different vaccination regimens on broiler chickens challenged with multidrug-resistant Escherichia coli and Salmonella

Abstract: The effects of a multistrain potential probiotic (Protexin®), acids, and a bacterin from multidrug-resistant E. coli O26, O78, S. Enteritidis (1,9,12 g.m1,7), and S. Typhimurium (1,4,5,12.i.1,2) on the immune response, haematological parameters, cytokines, and growth parameters of broiler chickens challenged with bacterin live serotypes were investigated. Two experiments were designed using 300 one-day-old chicks (Arbor Acres) randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The intestinal morphology is an important indicator of intestinal health, such as intestinal barrier integrity, nutrient digestion, and the absorption capacity of the small intestine ( Sabry Abd Elraheam Elsayed et al, 2021 ). In the present study, our results showed that the DEX challenge significantly damaged the intestinal morphology in the ileum of broilers, which was consistent with the results reported by previous studies ( De Grande et al, 2020 ; Berenjian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal morphology is an important indicator of intestinal health, such as intestinal barrier integrity, nutrient digestion, and the absorption capacity of the small intestine ( Sabry Abd Elraheam Elsayed et al, 2021 ). In the present study, our results showed that the DEX challenge significantly damaged the intestinal morphology in the ileum of broilers, which was consistent with the results reported by previous studies ( De Grande et al, 2020 ; Berenjian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common examples of probiotics is Protexin which is a commercially available multistrain potential probiotic [84]. The Protexin contained bacteria that showed antimicrobial activity against Salmonella Typhimurium LT2, E. coli NCFB 1989, Staphylococcus aureus NCTC 8532, E. faecalis NCTC 775, and Clostridium difficile ATCC 43,594 [85].…”
Section: Novel Engineered Probiotics/postbiotics/synbioticsmentioning
confidence: 99%
“…Protexin ® (Probiotics International Ltd., Lopen Head, Somerset, UK) is a multi-strain probiotic preparation containing seven bacterial and two yeast strains. This bacterial and fungal combination preparation has been proven to enhance the immune response to Newcastle disease virus, lower the counts of caecal Escherichia coli [ 23 ], improve growth performance, and lower the levels of proinflammatory cytokines in broilers challenged with multiple bacterial species including avian pathogenic E. coli , Salmonella enteritidis , and Salmonella typhimurium [ 24 ]. However, this specific preparation has not been evaluated in chickens exposed to Eimeria oocysts.…”
Section: Introductionmentioning
confidence: 99%